2006
DOI: 10.1111/j.1467-6486.2006.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Assessing Organizational Core Values*

Abstract:  The goal of this study is to offer a methodology for empirically assessing the core values of an organization. It uses means-end analysis in order to determine those values that organization members manifest in their daily behaviour, and which are not just espoused 'truisms'. The method is based on the sense members of an organization make of what they do. Sensemaking follows a means-end pattern, through which individual actions converge into central values. The values most central in this means-end s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 45 publications
0
50
0
Order By: Relevance
“…Thompson & Chen, 1998;Van Rekom et al, 2006), we decided to present both the complete HVM and the dominant chains separately. The complete HVM is drawn for purposes of analysis.…”
Section: Ladderingmentioning
confidence: 99%
“…Thompson & Chen, 1998;Van Rekom et al, 2006), we decided to present both the complete HVM and the dominant chains separately. The complete HVM is drawn for purposes of analysis.…”
Section: Ladderingmentioning
confidence: 99%
“…As a proxy for this, we shed light on the expressed values of the two organizations, even though we are aware that expressed values may diverge from actual values (cf. Argyris & Schön 1974;van Rekom 2006). Values can be seen as expressions of both what is desirable and what is worthy of protection, which means that values indicate the moral constraints that organizations place on their activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, identity features may be of a more general scope than concrete incident situations or distinctions emerging in a Kelly grid or critical incident episode situation. Therefore, in the spirit of the laddering technique (Reynolds and Gutman, 1984;van Rekom et al, 2006), participants respond to prompts regarding why the identified features matter to them, which helps establish the underlying dimensions of the organization's identity according to interviewees. The approach requires that interviewees explain their reasons many times; thus, they themselves synthesize what they are saying and name the features of their organization in a more abstract way.…”
Section: Preliminary Phasementioning
confidence: 99%